Quillaja brasiliensis nanoparticle adjuvant formulation improves the efficacy of an inactivated trivalent influenza vaccine in mice - Silveira, Fernando; Rivera-Patron, Mariana; Deshpande, Nikita; Sienra, Soledad; Checa, Jackeline; Moreno, María; Chabalgoity, Jose A.; Cibulski, Samuel P.; Baz, Mariana (Frontiers in Immunology, 2023)
The threat of viral influenza infections has sparked research efforts to develop vaccines that can induce broadly protective immunity with safe adjuvants that trigger robust immune responses. Here, we demonstrate that subcutaneous or intranasal delivery of a seasonal trivalent influenza vaccine (TIV) adjuvanted with the Quillaja brasiliensis saponin-based nanoparticle (IMXQB) increases the potency of TIV. The adjuvanted vaccine (TIV-IMXQB) elicited high levels of IgG2a and IgG1 antibodies with virus-neutralizing capacity and improved serum hemagglutination inhibition titers. The cellular immune response induced by TIV-IMXQB suggests the presence of a mixed Th1/Th2 cytokine profile, antibody-secreting cells (ASCs) skewed toward an IgG2a phenotype, a positive delayed-type hypersensitivity (DTH) response, and effector CD4+ and CD8+ T cells. After challenge, viral titers in the lungs were significantly lower in animals receiving TIV-IMXQB than in those inoculated with TIV alone. Most notably, mice vaccinated intranasally with TIV-IMXQB and challenged with a lethal dose of influenza virus were fully protected against weight loss and lung virus replication, with no mortality, whereas, among animals vaccinated with TIV alone, the mortality rate was 75%. These findings demonstrate that TIV-IMXQB improved the immune responses to TIV, and, unlike the commercial vaccine, conferred full protection against influenza challenge.